Ossification of the posterior longitudinal ligament in three geographically and genetically different populations of ankylosing spondylitis and other spondyloarthropathies. Issue 7 (1st July 1998) - Ramos-Remus, Cesar; Russell, Anthony S; Gomez-Vargas, Amparo; Hernandez-Chavez, Abel; Maksymowych, Walter P; Gamez-Nava, Jorge I; Gonzalez-Lopez, Laura; García-Hernández, Alicia; Meoño-Morales, Esther; Burgos-Vargas, Ruben; Suarez-Almazor, Maria E
Abstract : STUDY DESIGN: Cross sectional. RESEARCH QUESTIONS: (a) Is any clinical variable of ankylosing spondylitis (AS) associated with the presence of ossification of the posterior longitudinal ligament (OPLL)? and (b) Is OPLL present in patients with AS from different geographical or genetic backgrounds? METHODS: Three groups were assembled: (1) a prospective group of 103 consecutive AS patients from two community based rheumatology clinics from Guadalajara, who were evaluated using: a questionnaire with disease characteristic variables; clinical assessment by a neurologist; lateral radiographic views of the cervical spine and somatosensory evoked potentials (SSEP). (2) Fifty one spondyloarthropathies (SpA) patients from Mexico city whose cervical spine films were retrospectively reviewed. (3) Thirty nine AS patients from Edmonton, Canada whose cervical spine films were retrospectively reviewed and compared with 72 controls. RESULTS: Group 1: 74% of the 103 patients were men and 86% were HLA-B27 positive. The mean age was 35 years, and mean (SD) disease duration 10 (8) years. OPLL was reported in 16 patients (15.5%; 95%C I 9, 22). OPLL was statistically associated with older age (p=0.001), longer disease duration (p=0.001), clinical myelopathy (p=0.03), worst functional index (p=0.042), restricted axial movement measurements (all p<0.001), radiological sacroiliitis (p<0.001 for linear association), osteitis pubis (p=0.009), hip involvement (p=0.006 for linear association), and abnormal SSEP (p=0.008). Group 2: 92% of 51 patients were men; the mean age was 30 years and the mean (SD) disease duration 11 (7) years. OPLL was reported in 15 (29%, 95%CI 17, 41) patients (nine AS, two psoriatic arthritis, three juvenile AS, and one Reiter's syndrome). Group 3: 95% of the 39 patients were men; the mean of age was 46 years and disease duration of 18 (10) years. OPLL was reported in nine (23%; 95%CI 10, 36) patients, including one with psoriatic arthritis, and two with Crohn's disease. OPLL was observed in two of the control group. CONCLUSIONS: The prevalence of OPLL in AS and SpA is higher than previously recognised and seems to be associated with variables identifying more severe axial disease.